Soluble phenylpropanoids are involved in the defense response of Arabidopsis against Verticillium longisporum. Issue 3 (31st January 2014) - König, Stefanie; Feussner, Kirstin; Kaever, Alexander; Landesfeind, Manuel; Thurow, Corinna; Karlovsky, Petr; Gatz, Christiane; Polle, Andrea; Feussner, Ivo
Summary Verticillium longisporum is a soil‐borne vascular pathogen causing economic loss in rape. Using the model plant Arabidopsis this study analyzed metabolic changes upon fungal infection in order to identify possible defense strategies of Brassicaceae against this fungus. Metabolite fingerprinting identified infection‐induced metabolites derived from the phenylpropanoid pathway. Targeted analysis confirmed the accumulation of sinapoyl glucosides, coniferin, syringin and lignans in leaves from early stages of infection on. At later stages, the amounts of amino acids increased. To test the contribution of the phenylpropanoid pathway, mutants in the pathway were analyzed. The sinapate‐deficient mutant fah1‐2 showed stronger infection symptoms than wild‐type plants, which is most likely due to the lack of sinapoyl esters. Moreover, the coniferin accumulating transgenic plant UGT72E2‐OE was less susceptible. Consistently, sinapoyl glucose, coniferyl alcohol and coniferin inhibited fungal growth and melanization in vitro, whereas sinapyl alcohol and syringin did not. The amount of lignin was not significantly altered supporting the notion that soluble derivatives of the phenylpropanoid pathway contribute to defense. These data show that soluble phenylpropanoids are important for the defense response of Arabidopsis against V. longisporum and that metabolite fingerprinting is a valuable tool to identify infection‐relevant metabolic markers.